EXENTERATION OF THE SMALL PELVIS IN TREATMENT OF LOCAL TUMORS - N. A. Maistrenko; A. A. Khvatov; G. V. Uchvatkin; A. A. Sazonov (Вестник хирургии имени И.И. Грекова)
The authors analyzed the experience at the period from September 2000 to January 2014. The total exenterations of the small pelvis were performed on 23 patients (12 men and 11 women) at the age from 37 to 71 years old. Supralevator total exenterations with full visceral reconstruction were carried out in 13 cases out of 23. Total infralevator pelvic exenterations were used in 10 cases. There wasn’t the intraoperative lethality. Patients (3 cases) died in postoperative period. Postoperative complications developed in 10 patients, though serious complications, which required an application of surgical strategy were noted only in 3 cases. The mean life span consisted of 29 months. The performance of total exenteration of the small pelvis considerably increased the life span of the patients and in case of application of reconstructive methods allowed restoration of quality of life to high level and obtaining moral, psychological and social rehabilitation.